Sentence processing is modulated by the current linguistic environment and a priori information: An fMRI study - Weber, Kirsten (Brain Behav, 2019)
INTRODUCTION: Words are not processed in isolation but in rich contexts that are used to modulate and facilitate language comprehension. Here, we investigate distinct neural networks underlying two types of contexts, the current linguistic environment and verb‐based syntactic preferences. METHODS: We had two main manipulations. The first was the current linguistic environment, where the relative frequencies of two syntactic structures (prepositional object [PO] and double‐object [DO]) would either follow everyday linguistic experience or not. The second concerned the preference toward one or the other structure depending on the verb; learned in everyday language use and stored in memory. German participants were reading PO and DO sentences in German while brain activity was measured with functional magnetic resonance imaging. RESULTS: First, the anterior cingulate cortex (ACC) showed a pattern of activation that integrated the current linguistic environment with everyday linguistic experience. When the input did not match everyday experience, the unexpected frequent structure showed higher activation in the ACC than the other conditions and more connectivity from the ACC to posterior parts of the language network. Second, verb‐based surprisal of seeing a structure given a verb (PO verb preference but DO structure presentation) resulted, within the language network (left inferior frontal and left middle/superior temporal gyrus) and the precuneus, in increased activation compared to a predictable verb‐structure pairing. CONCLUSION: In conclusion, (1) beyond the canonical language network, brain areas engaged in prediction and error signaling, such as the ACC, might use the statistics of syntactic structures to modulate language processing, (2) the language network is directly engaged in processing verb preferences. These two networks show distinct influences on sentence processing.